ANALISIS RESEPSI KHALAYAK TENTANG STIGMA ORANG AUTISME DALAM DRAMA KOREA NETFLIX EXTRAORDINARY ATTORNEY WOO - Alifia Sekarningrum Wiharjo (2023)
Film and television series can serve as a means for individuals to instill new values and understanding and change others' perceptions of certain issues. For instance, the issue of stigma towards individuals with autism portrayed in the Korean drama Extraordinary Attorney Woo on Netflix. As an active audience, they can interpret the constructed messages in the Korean drama differently regarding the stigmatization of individuals with autism. This research aims to explore the audience's reception towards the stigma of individuals with autism in the Korean drama Extraordinary Attorney Woo on Netflix, as well as the factors influencing the audience's reception. This research adopts a qualitative descriptive approach within the constructivist paradigm, employing Stuart Hall's reception analysis method, resulting in three categories of audience reception: dominant hegemonic, negotiation, and oppositional. The snowball sampling technique was employed for sample selection. The findings of this research indicate that out of seven informants, four hold a position of dominant hegemonic reception, while three are in a negotiation position. Informants in the negotiation position construct meanings related to the forms of stigma towards individuals with autism depicted in the drama as something that still commonly occurs or is considered acceptable, given that the real-world situation may not be as idealized as portrayed in the Korean drama. The factors influencing informants' reception in this study include similar backgrounds in terms of age, education, residence, as well as experience and knowledge regarding autism. This is due to the fact that individuals residing in urban areas, with higher educational backgrounds, and exposure to various media contents, including films/series and social media, tend to have a higher tolerance towards differences compared to those who do not. Through this research, the researcher hopes that media such as television series and films can better address the issue of autism, leading to a shift in societal perceptions away from viewing individuals with autism as objects of ridicule, incompetence, or worthless.